2009
DOI: 10.1108/10662240910927795
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the appeal of user‐generated media: a uses and gratification perspective

Abstract: PurposeUser‐generated media (UGM) like YouTube, MySpace, and Wikipedia have become tremendously popular over the last few years. The purpose of this paper is to present an analytical framework for explaining the appeal of UGM.Design/methodology/approachThis paper is mainly theoretical due to a relative lack of empirical evidence. After an introduction on the emergence of UGM, this paper investigates in detail how and why people use UGM, and what factors make UGM particularly appealing, through a uses and grati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
633
2
54

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 831 publications
(777 citation statements)
references
References 52 publications
20
633
2
54
Order By: Relevance
“…Also the establishment of a network connection on SNS has been described as participating usage [7]. The highest level of interaction is production, and describes the creation and publication of contents in the form of text, images, audio and video [23].…”
Section: Web 20 Usage Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the establishment of a network connection on SNS has been described as participating usage [7]. The highest level of interaction is production, and describes the creation and publication of contents in the form of text, images, audio and video [23].…”
Section: Web 20 Usage Typesmentioning
confidence: 99%
“…However, it can be argued that SNS allow for a variety of different usage types which can be further specified. Therefore, our models apply Shao's [23] conceptualization of audience activity on a continuum of interaction from low to high. The author differentiates three usage types for user-generated media (UGM): consumption, participation and production.…”
Section: Web 20 Usage Typesmentioning
confidence: 99%
“…Madell and Muncer (2007) while researching people aged 18-20 on why they chose to use certain communication media, especially the Internet and mobile phones for social purposes discovered participants indicated that different communication media afforded them differing levels of control over their social interactions. Research by Shao (2009) into the popularity of user-generated media (UGM) sites such as YouTube, MySpace, and Wikipedia showed that one of the reasons behind the popularity was the sense of control users have over the creation and sharing of content. Traditional marketing campaigns targeted at younger alumni may not be successful because these individuals like control over their social interactions and want the ability to engage in conversation and content creation, something the social media environment can offer.…”
Section: Alumnimentioning
confidence: 99%
“…It was originally applied to television viewing and the usage of traditional media (e.g., Conway and Rubin, 1991). Modified versions of the U&G approach have been successfully applied to new interactive media (e.g., Dimmick et al, 2000;Ferguson and Perse, 2000;LaRose et al, 2001;Ruggiero, 2000;Stafford et al, 2004) including social media (e.g., Shao, 2009). Six motives have been identified as especially relevant to social media usage (Shao, 2009;Courtois et al, 2009), namely information, entertainment, social interaction, community development, self-expression, and self-actualisation.…”
Section: Uses and Gratification Approachmentioning
confidence: 99%
“…These motives can be related to different activities in social media. According to Shao (2009) there are three separate but interdependent usages of social media: Consuming (for information and entertainment uses), participating (for social interaction and community development uses), and producing (for self-expression and self-actualisation uses). Other conceptions of motives for the use of Web 2.0 are very similar (Park et al, 2009;Krishnamurthy and Dou, 2008).…”
Section: Uses and Gratification Approachmentioning
confidence: 99%